(untitled) (Canadian Hematology Today, 2025)
The B-cell receptor (BCR) signaling pathway is a key driver in the development of B-cell malignancies, such as chronic lymphocytic leukemia (CLL), Waldenstrom’s macroglobulinemia (WM), mantle cell lymphoma (MCL) and marginal zone lymphoma (MZL), by promoting abnormal proliferation and survival. Antigen binding to the BCR triggers activation of Bruton’s tyrosine kinase (BTK), which in turn leads to activation of the nuclear factor kappa-B (NFκB) pathway, leading to nuclear translocation of NF-κB transcription factors. The essential role of BTK activation in BCR signaling highlights the rationale for BTK inhibition as a targeted therapeutic intervention in B-cell malignancies, effectively suppressing BCR signaling and limiting B-cell proliferation and survival.